Translation and the poet's life the ethics of translating in English culture, 1646-1726 - Davis, Paul 1968- (Oxford University Press, 2008)
Paul Davis explores the personal and cultural significances of translating as a distinctive mode of imaginative conduct for the five principal poet-translators of what was the golden age of the art in England: John Denham, Henry Vaughan, Abraham Cowley John Dryden, and Alexander Pope.